2007
DOI: 10.1002/ar.20584
|View full text |Cite
|
Sign up to set email alerts
|

Appearance of Crypt Neurons in the Olfactory Epithelium of the Skate Raja clavata During Development

Abstract: Crypt neurons are olfactory receptor cells located in the olfactory epithelium of fishes. They exhibit a peculiar and well-recognizable morphology, although their odorant specificity is still unknown. Data on their appearance during development are few and far between. This study set out to identify the time at which crypt neurons appeared in the skate, Raja clavata, using histological and immunohistochemical methods. For this purpose, embryos and juveniles at different stages of development, from 13 weeks aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 29 publications
(27 reference statements)
3
24
0
Order By: Relevance
“…Crypt olfactory sensory neurons are intensely labeled only by LEA and very weakly by WGA in contrast with the intense reaction obtained in the other receptor cells and in the mucous layer. Instead, lectin binding in Verasper moseri and in the elasmobranches Scyliorhinus canicula and Raja clavata demonstrated a high density of glycoconjugates in the cryptlike zone, reactive for PHA-L (Verasper moseri), specific for b-N-acetylgalactosamine, PNA (Scyliorhinus canicula), specific for b-galactose, and WGA (Scyliorhinus canicula and Raja clavata) Yamamoto et al, 2004;Ferrando et al, 2006Ferrando et al, , 2007, suggesting a wide range of odorant-receptor interactions. The almost complete absence of lectin binding we observed in the crypt cells of guppies could imply a limited glycosilation of transmembrane proteins or a reduced amount of glycoconjugates in the mucus and, as a consequence, a restricted odorant detection capability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crypt olfactory sensory neurons are intensely labeled only by LEA and very weakly by WGA in contrast with the intense reaction obtained in the other receptor cells and in the mucous layer. Instead, lectin binding in Verasper moseri and in the elasmobranches Scyliorhinus canicula and Raja clavata demonstrated a high density of glycoconjugates in the cryptlike zone, reactive for PHA-L (Verasper moseri), specific for b-N-acetylgalactosamine, PNA (Scyliorhinus canicula), specific for b-galactose, and WGA (Scyliorhinus canicula and Raja clavata) Yamamoto et al, 2004;Ferrando et al, 2006Ferrando et al, , 2007, suggesting a wide range of odorant-receptor interactions. The almost complete absence of lectin binding we observed in the crypt cells of guppies could imply a limited glycosilation of transmembrane proteins or a reduced amount of glycoconjugates in the mucus and, as a consequence, a restricted odorant detection capability.…”
Section: Discussionmentioning
confidence: 99%
“…Fish possess three different types of olfactory neurons and they have different apical surface, localization of the soma and length of the dendrite (Morita and Finger, 1998;Hamdani and Døving, 2007). Besides ciliated and microvillous receptor cells (Hansen and Zeiske, 1998;Farbman, 2000), common to all other vertebrates, new egg-shaped receptor neurons, the crypt cells, have been discovered in actinopterygean fish (Hansen et al, 1997;Hansen and Finger, 2000) and, recently, in some Chondrichthyes (Ferrando et al, 2006(Ferrando et al, , 2007. These cells are localized in the upper portion of the olfactory epithelium and bear both microvilli and cilia.…”
Section: Introductionmentioning
confidence: 99%
“…Despite an involvement in reproductive behaviour which has been suggested for this kind of RNs (Hamdani and Døving, 2006;Hamdani et al, 2008), studies on their electrophysiological properties in teleost suggest their response to amino acids, generally thought to mediate feeding behaviour (Schmachtenberg, 2006;Vielma et al, 2008). In Chondrichthyes, their involvement in reproduction has been ruled out by their early appearance during the development in Raja clavata (Ferrando et al, 2007b). Our data suggest that the G-protein alpha subunit type expressed by microvillous ORNs in S. canicula differs from that expressed in the CNs, highlighting their different function.…”
Section: Discussionmentioning
confidence: 99%
“…The olfactory system of Chondrichthyes has been studied mainly from a morphological point of view (Ebbesson and Heimer, 1970;Theisen et al, 1986;Franceschini and Ciani, 1993;Takami et al, 1994;Ferrando et al, 2006aFerrando et al, ,b, 2007a; its development has been only partially described (Fishelson and Baranes, 1997;Ferrando et al, 2007b;Ferrando, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Their presence in salmonids was first demonstrated by Sandahl and co-workers (Sandahl et al, 2006). Subsequent immunohistochemical studies reported the presence of crypt-cell-like cells in the olfactory epithelium of cartilaginous fish, the elasmobranch Scyliorhinus canicula and the skate Raja clavata (Ferrando et al, 2006;Ferrando et al, 2007;Ferrando et al, 2010), suggesting that the evolutionary emergence of olfactory crypt cells represents an ancient feature in vertebrate development. Interestingly, thus far crypt cells have been found solely in fishes, as opposed to amphibians or other aquatic animals, suggesting that they are an exclusive attribute of this large and diverse animal group.…”
Section: Introductionmentioning
confidence: 96%